DEVELOPMENT OF WEB-BASED LEARNING MEDIA ON CLASS X VIRUS MATERIAL - Setia Ningsih; Tika Mayang Sari (BIOTIK: Jurnal Ilmiah Biologi Teknologi dan Kependidikan, 2024)
Based on the results of the pre-survey that has been carried out at SMA Negeri 1 Kotagajah, a problem was found, namely the use of learning media that is lacking during teaching and learning activities on biological material including virus material. In teaching and learning activities, the educational media used are limited to Student Worksheets (LKPD) and Power Point. This resulted in some students having difficulty understanding the information and losing interest in biology. Scientists then developed a learning platform based on viral content available to Class X students via the Internet. The five stages of the ADDIE model are analysis, design, development, implementation, and evaluation. Percentage results of 80%, 87%, 94% and 85% were obtained from material expert, media expert, teacher and student validators. Students indicated that the use of web-based learning materials about viruses was "very feasible".